Light-induced beneficial ion accumulation for high-performance quasi-2D perovskite solar cells. Issue 6 (6th May 2022) - Lian, Xiaomei; Zuo, Lijian; Chen, Bowen; Li, Biao; Wu, Haotian; Shan, Shiqi; Wu, Gang; Yu, Xuegong; Chen, Qi; Chen, Liwei; Yang, Deren; Cahen, David; et al.
Abstract : 2D PVSCs with "favorable" ion accumulation are realized via thermal–light post-treatment, which increases the built-in potential and device performance. Abstract : Ion migration and subsequent accumulation at interfaces, driven by the built-in potential ( V bi ), are intrinsic properties of halide perovskite solar cells (PVSCs), which mostly decrease the device performance. To address this issue, we constructed favorable ion accumulation in perovskite solar cells via illumination to improve the performance of the quasi-2D PVSCs. This design dramatically improves the photo-carrier collection and enables significant device performance improvement from 14.6% to 19.05%, one of the best results for quasi-2D PVSCs. We argue that the light-triggered favorable ion accumulation originates from (1) the photo-induced quasi-Fermi level splitting that compensates the V bi, so as to avoid the ion accumulation that decreases V bi, and (2) the light-intensity-distribution-induced uneven ion potential further drives the segregation of mobile ions towards favorable ion accumulation, decreasing any I − gradient between the anode and cathode. Our work provides insight into the fundamental understanding of ion accumulation in perovskite-based optoelectronic devices and paves the way to more stable, high-performance PVSCs.